2011
DOI: 10.1016/j.baae.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, landscape scale responses in riparian tundra vegetation to exclusion of small and large mammalian herbivores

Abstract: 21Productive tundra plant communities composed of a variety of fast growing herbaceous and 22 woody plants are likely to attract mammalian herbivores. Such vegetation is likely to respond 23 to different-sized herbivores more rapidly than currently acknowledged from the tundra. 24Accentuated by currently changing populations of arctic mammals there is a need to 25 understand impacts of different-sized herbivores on the dynamics of productive tundra plant 26 communities. Here we assess the differential effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 47 publications
7
92
0
Order By: Relevance
“…We suspect that the negative responses in these insectivorous birds result from halted spatial spillover of food resources from the rich fauna of insects dwelling in the willow thickets (den Herder et al, 2004) onto the surrounding open habitats. However, we cannot exclude that even changed composition of the non-woody components of the meadow vegetation resulting from intense reindeer grazing (Ravolainen et al, 2011) (Post andPedersen, 2008, Olofsson et al, 2009). This proposal is motivated by the expectation that large-scale shrub encroachment will cause positive feedbacks on global climate warming though biophysical processes (Chapin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that the negative responses in these insectivorous birds result from halted spatial spillover of food resources from the rich fauna of insects dwelling in the willow thickets (den Herder et al, 2004) onto the surrounding open habitats. However, we cannot exclude that even changed composition of the non-woody components of the meadow vegetation resulting from intense reindeer grazing (Ravolainen et al, 2011) (Post andPedersen, 2008, Olofsson et al, 2009). This proposal is motivated by the expectation that large-scale shrub encroachment will cause positive feedbacks on global climate warming though biophysical processes (Chapin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…1C). A recent exclosure experiment has shown that such willow ramets in riparian meadows in this study region are severely suppressed due to intense browsing (Ravolainen et al, 2011). The level of browsing even in the riparian habitats with willow thickets was high enough to cause substantial fragmentation of the willow thickets (Fig.…”
Section: Study System and Designmentioning
confidence: 99%
“…Although overgrazing can occur even during low population density (Virtanen et al 1997), lemmings have mainly been observed to overgraze their habitats at high population density (Oksanen and Oksanen 1981;Moen et al 1993): for instance, Moen et al (1993) found that lemming grazing decreased the cover of graminoids by 33%, and mosses by 66% during a peak year. Moreover, plant biomass increases substantially over time in exclosures without rodent grazing (Virtanen et al 1997;Ravolainen et al 2011) and a study using satellite imagery in northern Sweden showed that the impact of lemmings on plant biomass is strong enough to be visible from space (Olofsson et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Snow affects the micro-climate which creates ecological niches for different plants (Ravolainen et al 2011). For example, snow bed habitat has a high richness of plants, similar to that in locally more productive habitats (Bruun et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation